2022
DOI: 10.1007/s10995-022-03391-9
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Practices on the Prevention and Management of Diarrhea in Children Under-2 Years Among Women Dwelling in Urban Slums of Karachi, Pakistan

Abstract: Background Diarrhea is the second leading cause of death especially among children. The age-proportionate mortality of diarrheal disease in infants under 2 years is 72%, among children under 5 years of age. Children living in urban slums are more prone to develop diarrhea. Although the disease can be prevented by many simple cost-effective interventions, i.e. proper sanitation and hygiene, appropriate feeding, and timely vaccination, poverty and lack of basic life amenities often potentiate diarr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 37 publications
(42 reference statements)
1
10
1
1
Order By: Relevance
“…Lack of association between various types of SBF and CFM in our study might be due to the cross-sectional study design and social desirability bias, or overreporting of socially desirable behaviors during an interview and survey [49]. The social desirability biasness of the participants can be controlled by conducting indirect questioning, qualitative research and intervention trials [50,51].…”
Section: Discussionmentioning
confidence: 84%
“…Lack of association between various types of SBF and CFM in our study might be due to the cross-sectional study design and social desirability bias, or overreporting of socially desirable behaviors during an interview and survey [49]. The social desirability biasness of the participants can be controlled by conducting indirect questioning, qualitative research and intervention trials [50,51].…”
Section: Discussionmentioning
confidence: 84%
“…Similarly, the cultural practice of food abstinence during diarrhoeal illness and lack of maternal knowledge about diarrhoea case management also contributes to the low adherence (34). Different studies conducted in Pakistan reflected that most mothers are well-aware of zinc and ORS use for managing paediatric diarrhoea (18,35,36). However, a study conducted in the urban slums of Karachi reported inappropriate diarrhoea case management practices despite having adequate knowledge regarding diarrhoea case management (18).…”
Section: Discussionmentioning
confidence: 99%
“…Different studies conducted in Pakistan reflected that most mothers are well-aware of zinc and ORS use for managing paediatric diarrhoea (18,35,36). However, a study conducted in the urban slums of Karachi reported inappropriate diarrhoea case management practices despite having adequate knowledge regarding diarrhoea case management (18). The knowledge-practice gap for diarrhoea case management can be averted by performing ethnographic studies, and these ethnographic studies would explore the underlying barriers to diarrhoea case management among Pakistani children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sementara pengetahuan di antara wanita tentang langkah-langkah pencegahan untuk diare anak tidak cukup, terjemahan pengetahuan yang tepat ke dalam praktik yang tepat menunjukkan hasil yang menjanjikan untuk mengurangi morbiditas diare. Pendekatan terpadu untuk meningkatkan praktik pemberian makan, sanitasi, dan kebersihan bersama dengan pendidikan kesehatan berkelanjutan dapat mengurangi beban diare di antara bayi yang tinggal di daerah kumuh perkotaan (Khaliq et al, 2022). Piperlukan kolaborasi lebih lanjut antara pemerintah dan lembaga swadaya masyarakat untuk mengidentifikasi faktor-faktor penularan diare yang masih ada di berbagai komunitas di wilayah tersebut (Mekonnen et al, 2019).…”
Section: Pembahasanunclassified